Technology Acceptance Model (TAM) untuk Menganalisis Penerimaan Pengguna Terhadap Penggunaan Aplikasi Belanja Online XYZ - Desi Pibriana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
The development of technology and information in this day especially the internet experiencing very rapid development. The internet connects one person to another, provide information, as a means of entertainment, and as a means of communication. XYZ Online shopping application is an application from PT. XYZ that is used to sell products online. After a simple survey of 50 people, as many as 13 people are XYZ Online shopping application users and have positive opinions. To find out more about whether the opinions of these 13 people represent the opinions of XYZ Online shopping application users as a whole, then you need to know the level of user acceptance of Online shopping application, to find out the level of user acceptance, the Technology Acceptance Model (TAM) method is used. In conducting data collection, the authors use survey research with a sample of 365 respondents and for data analysis, the tools used are SPSS software to test the validity and reliability of variable instruments and SmartPLS to test the model. The results of this study are of the 7 hypotheses proposed, the seven hypotheses can be accepted and have a positive effect.